2005
DOI: 10.1042/cs20040278
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron deficiency induces ventricular dilation, mitochondrial ultrastructural aberrations and cytochrome c release: involvement of nitric oxide synthase and protein tyrosine nitration

Abstract: Iron deficiency is associated with multiple health problems, including the cardiovascular system. However, the mechanism of action of iron-deficiency-induced cardiovascular damage is unclear. The aim of the present study was to examine the effect of dietary iron deficiency on cardiac ultrastructure, mitochondrial cytochrome c release, NOS (nitric oxide synthase) and several stress-related protein molecules, including protein nitrotyrosine, the p47phox subunit of NADPH oxidase, caveolin-1 and RhoA. Male weanlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 37 publications
5
130
0
2
Order By: Relevance
“…Increased oxidative stress likely further compounds this effect. Similar, albeit milder changes, have been described in IDA animal models (59,60,75,76). It may be that these changes are more severe in SCA because of the added disadvantage of sickling in the microvasculature and increased oxidative stress, both evident in our transcriptome analyses.…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening supporting
confidence: 48%
“…Increased oxidative stress likely further compounds this effect. Similar, albeit milder changes, have been described in IDA animal models (59,60,75,76). It may be that these changes are more severe in SCA because of the added disadvantage of sickling in the microvasculature and increased oxidative stress, both evident in our transcriptome analyses.…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening supporting
confidence: 48%
“…Experimental studies have shown that ID induced cardiac dysfunction13 and cardiac hypertrophy, characterized by aberrant mitochondrial and irregular sarcomere organization 14…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that iron deficiency (ID) led to structural and functional abnormalities of the heart 3. In humans, a small report showed a reduction in iron content of cardiomyocytes of patients with HFrEF compared with controls 4.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac muscle examined by transmission electron microscopy showed mitochondrial swelling and abnormal sarcomere structure. 15 In another study, iron deficiency was associated with impairment of myocardial mitochondrial electron transport in rat heart. 16 …”
Section: Experimental Evidence With Iron and Muscle Functionmentioning
confidence: 99%
“…Two studies fed iron-deficient diets to rats and examined cardiac muscle. 15,16 Rats receiving iron-deficient diet were anemic. Cardiac muscle examined by transmission electron microscopy showed mitochondrial swelling and abnormal sarcomere structure.…”
Section: Experimental Evidence With Iron and Muscle Functionmentioning
confidence: 99%